Die Anbahnung einer forschenden Grundhaltung im Verlauf des Praxissemesters: Entwicklungsverläufe und Gelingensbedingungen - Homt, Martina; van Ophuysen, Stefanie

Elternsorgen und Kindersorgen während der Corona-Pandemie - Sander, Andreas; van Ophuysen, Stefanie; Schäfer, Laura; Homt, Martina

Forming Simulation of Tailored Press Hardened Parts - Triebus, Marcel; Reitz, Alexander; Grydin, Olexandr; Grenz, Julian; Schneidt, Andreas; Erhardt, Rüdiger; Tröster, Thomas; Schaper, Mirko (13th European LS-DYNA Conference 2021)

Steigerung der Prognosegüte mechanischer Fügeprozesssimulationen durch den Einsatz einer fügespezifischen Reibmodellierung basierend auf einer experimentellen Parametrisierung - Rossel, Moritz Sebastian; Meschut, Gerson (11. Fügetechnisches Gemeinschaftskolloquium)

Motivationsregulationsformen zum Erwerb pädagogisch-psychologischer Theorien und Befunde im Lehramtsstudium - Grosser, Christine; Wehde, Janis

Die Reflexion der eigenen Lehrtätigkeit von Studierenden in Praxisphasen durch Forschendes Lernen: Prädiktiver Einfluss subjektiver Normen im schulischen und universitären Kontext - Wehde, Janis; Bloh, Bea

Fiber response to pin penetration in dry woven fabric using numerical analysis - Droß, M.; Heyser, Per; Meschut, Gerson; Hürkamp, A.; Dröder, K. (Journal of Advanced Joining Processes)

Großserientaugliche induktive Platinenerwärmung für den Warmformprozess - Tröster, Thomas; Pfeifer, Florian; Nacke, Bernard; Dietrich, André

Kollektive Reflexionsphasen - Bloh, Thiemo

IT-Systeme für das Krisenmanagement - Pottebaum, Jens; Schäfer, Christina (Sicherheitskritische Mensch-Computer-Interaktion)

Die Zukunft sicherheitskritischer Mensch-Computer-Interaktion - Reuter, Christian; Aal, Konstantin; Beham, Frank; Boden, Alexander; Brauner, Florian; Fiedrich, Frank; Fuchs-Kittowski, Frank; Geisler, Stefan; Gennen, Klaus; Herrmann, Dominik; Kaufhold, Marc-André; Klafft, Michael; et al. (Sicherheitskritische Mensch-Computer-Interaktion)

Supporting Innovation Management for SMEs: A Tool for Idea Selection - Gräßler, Iris; Koch, Anna-Sophie; Thiele, Henrik; Dattner, Michael (Proceedings of the ISPIM Innovation Conference)
In innovation management, usually there is a large number of product ideas, not all of which meet the requirements of a company and make sense to pursue further. For selecting the most promising ideas, several methods exist which each focus on a certain aspect. Due to the characteristics of Small and Medium Enterprises (SMEs) such as limited resources, these enterprises have special requirements on methods for selecting ideas. In this study, criteria of SMEs for idea selection are deducted from SME-characteristics. Methods for idea selection are tested for fulfillment of these criteria and the results are combined in a matrix. Together with a guideline, a tool for idea selection in innovation management of SMEs is developed. The results are validated in the context of innovation management in SMEs. By selecting a method, a SME is enabled to make economically viable decisions for their product portfolio, thus ensuring sustainable economic success.
Keywords: innovation management; SME; evaluation method; idea selection; meta-study; idea evaluation

Produktspezifische Optimierung der Nachhaltigkeit im Ersatzteilmanagement. Ganzheitliche Vorgehensweise zur Bewertung der Nachhaltigkeit additiv gefertigter Komponenten für den Aftermarket - Gräßler, Iris; Hillebrand, Stefan; Thiele, Henrik (Digitalisierung im Kontext von Nachhaltigkeit und Klimawandel)
Um der ansteigenden Erderwärmung entgegenzuwirken, erheben immer mehr Regierungen Steuern und Strafzahlungen auf den CO2-Ausstoß. Dieses betrifft auch die Ersatzteil¬versorgung im Automobilbereich. Dabei muss bislang dem Bedarf vorgelagert produziert werden, was mit hohen Lagerkapazitäten und logistischen Aufwänden verbunden ist. CO2-Einsparungen sind daher durch einen Wechsel auf die additive on-demand-Fertigung über ein dezentrales Fertigungsnetzwerk aus Lohndienstleistern möglich. Allerdings ist die dezentrale Ersatzteilfertigung trotz Einbezug des CO2-Preises nicht in jedem Fall wirtschaftlich. Der Grund hierfür liegt in der Abhängigkeit der Gesamtkosten von Faktoren wie Bauteilgeometrie, Logistikaufwand und Stückzahl. Im vorliegenden Beitrag wird eine Vorgehensweise für den Vergleich einer zentralen mit einer dezentralen Ersatzteilversorgung durch die Ergänzung relevanter, produktspezifischer Kennwerte für die additive Bauteilfertigung beschrieben. Neben der Ökobilanz berücksichtigt die entwickelte Methode die wirtschaftliche Rentabilität des Herstellungsverfahrens. Die Validierung dieser Vorgehensweise erfolgt in Kooperation mit einem deutschen Automobilhersteller. Die entwickelte Vorgehensweise dient Automobilherstellern als Entscheidungsunterstützung bei der Fragestellung, ob einzelne Ersatzteilkomponenten herkömmlich oder additiv gefertigt werden.

Should I stay or should I go? The dark side of corporate entrepreneurship - Tomin, Slawa; Krebs, Benjamin (Frontiers of Entrepreneurship Research)

HRM in the Germanic context - Krebs, Benjamin; Wach, Bernhard Alexander; Wehner, Marius Claus; Reichel, Astrid; Mayrhofer, Wolfgang; Sender, Anna; Staffelbach, Bruno; Ligthart, Paul (Handbook on contextual approaches to human resource management)

Aus der Forschung in die Anwendung - Materialqualifizierung im Kunststoff Freiformen - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Kunststoffland NRW report)

Fluid Dynamics of the Open Port Interface for High-Speed Nanoliter Volume Sampling Mass Spectrometry - Liu, Chang; Van Berkel, Gary J.; Kovarik, Peter; Perot, J. Blair; Inguva, Venkatesh; Covey, Thomas R. (Analytical Chemistry)

Analyzing Approximate Value Iteration Algorithms - Ramaswamy, Arunselvan; Bhatnagar, Shalabh (Mathematics of Operations Research (to appear))

Automated Detection of Side Channels in Cryptographic Protocols: DROWN the ROBOTs! - Drees, Jan Peter; Gupta, Pritha; Hüllermeier, Eyke; Jager, Tibor; Konze, Alexander; Priesterjahn, Claudia; Ramaswamy, Arunselvan; Somorovsky, Juraj (14th ACM Workshop on Artificial Intelligence and Security)

Deep Q-Learning: Theoretical Insights from an Asymptotic Analysis - Ramaswamy, Arunselvan; Hüllermeier, Eyke (IEEE Transactions on Artificial Intelligence (to appear))

Weiterentwicklung von GITBlow für dünnwandige Hohlstrukturen auf Organoblechen - Moritzer, Elmar; Kröker, Michael (CU reports)

Simulative analysis of the filling process in the 2K GITBlow process on organo sheets - Moritzer, Elmar; Kröker, Michael

Validation of an Online State Estimation Concept for Microscopic Traffic Simulations◆ - Malena, Kevin; Link, Christopher; Mertin, Sven; Gausemeier, Sandra; Trächtler, Ansgar (2021 IEEE Transportation Electrification Conference & Expo (ITEC))
This paper deals with a novel method for the online fitting of a microscopic traffic simulation model to the current state of a real world traffic area. The traffic state estimation is based on limited data of different measurement sources and guarantees general accordance of reality and simulation in terms of multimodal road traffic counts and vehicle speeds. The research is embedded in the challenge of improving the traffic by controlling the traffic light systems (TLS) of the examined area. Therefore, the current traffic state and the predicted route choices of individual road users are the matter of interest. The concept is generally transferable to any road traffic system. To give an impression of the accuracy and potential of the approach, the validation and first application results are presented.

Einfluss eines beheizten Bauraums auf die Schweißnahtqualität - Moritzer, Elmar; Wächter, Julian (Plastverarbeiter)

Tensor-based computation of metastable and coherent sets - Nüske, Feliks; Gelß, Patrick; Klus, Stefan; Clementi, Cecilia (Physica D: Nonlinear Phenomena)

Symmetric and antisymmetric kernels for machine learning problems in quantum physics and chemistry - Klus, Stefan; Gelß, Patrick; Nüske, Feliks; Noé, Frank (Machine Learning: Science and Technology)

Pulverherstellung und Verrundung neuer Polymermaterialien für das selektive Lasersintern (SLS) - Poster - Ponusamy, SathishKumar

A model for the carbon fiber breakage along the twin‐screw extruder - Malatyali, Hatice; Schöppner, Volker; Rabeneck, Nils; Hanselle, Felix; Austermeier, Laura; Karch, David (SPE Polymers)

The Influence of Process Conditions on the Fiber Length Reduction for Recycled Carbon Fibers - Malatyali, Hatice; Schöppner, Volker; Lochbaum, Ella; Bomm, Igor; Hanselle, Felix (SPE ANTEC)

Reproducibility analysis of fiber length measurements during processing with twin screw extruders - Malatyali, Hatice; Schöppner, Volker; Akar, Seyit Ali; Hanselle, Felix; Austermeier, Laura (SPE ANTEC)

The Hare and the Hedgehog: Empirical evidence on the relationship between the individual Pace of Life and the speed-accuracy continuum - Hoffmann, Christin; Hoppe, Julia Amelie; Ziemann, Niklas (PloS one)

The relationship between talent management and individual and organizational performance - Krebs, Benjamin; Wehner, Marius Claus (The Routledge companion to talent management)

Lebensdauer vorhersagen? - Gevers, Karina; Schöppner, Volker (K-Zeitung)
Keywords: Infrarotschweißen; Glasfaserverstärkte Kunststoffe; Lebensdauer; Langzeitbelastung

Heated tool butt welding of two different materials – Established methods versus artificial intelligence - Gevers, Karina; Schöppner, Volker; Hüllermeier, Eyke

Development of scale up rules for quasi-simultaneous laser transmission welding of thermoplastics - Arndt, Theresa; Schöppner, Volker

Design and Experimental Investigation of an Additively Manufactured PMSM Rotor - Urbanek, Stefan; Pauline, Frey; Magerkohl, Sebastian; Zimmer, Detmar; Tasche, Lennart; Schaper, Mirko; Ponick, Bernd
Keywords: Elektromotor; Elektromaschine; Additive Fertigung; AF; AM; Additive Manufacturing; DMRC; KAt

3D-Druck in der industriellen Anwendung - Funktions- und fertigungsgerechte Konstruktion mit additiver Fertigung (Vortrag) - Magerkohl, Sebastian; Brüggemann, Jan-Peter

DEVELOPMENT OF A NEW METHOD TO EVALUATE THE DISTRIBUTIVE MIXING QUALITY BASED ON THE PARTICLE TRACKING METHOD AND THE DELAUNAY TRIANGULATION - Frank, Maximilian; Schöppner, Volker (ANTEC® 2021)

Influence of angled dispersion gas on coaxial atomization, spray and flame formation in the context of spray-flame synthesis of nanoparticles - Bieber, M.; Al-Khatib, M.; Fröde, F.; Pitsch, H.; Reddemann, M. A.; Schmid, H-J.; Tischendorf, R.; Kneer, R. (Experiments in Fluids)
Liquid atomization determines the initial conditions for flame formation and particle synthesis. Without a stable flame, high droplet velocities and thus short droplet residence time in the flame may lead to droplets being injected into an extinguished flame, which influences synthesis and final particle output. An experimental investigation of spray formation and flame stability is performed through high-speed visualization. Targeted variation of nozzle geometry is applied to improve spray-flame interaction and compared to a standardized burner. Timescales of spray density and flame fluctuations are quantified and compared, where the latter were significantly larger and hence not correlated. Instead, dispersion gas forms a barrier between spray phase and pilot flame; hence, ignition depends on large liquid lumps with high radial momentum to break through the dispersion gas for spray ignition. Angling of dispersion gas flow increases radial shear and turbulence and leads to refined atomization and improved flame stability. To investigate the nozzle influence on particle formation, particle characteristics are examined by online and offline analytics with focus on particle structures and product purity. The modified nozzle produced smaller primary particle sizes, thus indicating a sensitivity of sintering dominance on the nozzle geometry. Impurities impact the examination of particle structures and general particle functionality. Carbon contamination was apparent in synthesized particles and also indicated sensitivity to nozzle geometry. Discrepancies to literature data are discussed regarding differences in flame activity and droplet characteristics. The report highlights, how product characteristics can differ crucially due to changes in nozzle geometry despite comparable operating conditions.

Separation of Multi-Component Parts for Mechanical Recycling – An Approach to Produce Hard-Soft Combinations with a Better Recyclability - Hopp, Matthias; Mühlhoff, Frederik Marvin (79th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

Transitioning to Condition-Based Maintenance on the Distribution Grid: Deriving Design Principles from a Qualitative Study - zur Heiden, Philipp; Priefer, Jennifer (Pre-Conference 16th International Congress on Wirtschaftsinformatik at Universität Duisburg-Essen)

Constructions of a National Threat: Contextualising the Rhetorical Management of the COVID-19 Pandemic in Britain - Tönnies, Merle (Mentalities and Materialities: Essays in Honour of Jürgen Kamm)

Faster, harder, greener? Empirical evidence on the role of the individual Pace of Life for productivity and pro-environmental behavior - Hoffmann, Christin; Hoppe, Julia Amelie; Ziemann, Niklas (Ecological Economics)

Kleine Tropfen, große Wirkung - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Kunststoffe)

Assessment of AlZnMgCu alloy powder modification for crack-free laser powder bed fusion by differential fast scanning calorimetry - Zhuravlev, Evgeny; Milkereit, Benjamin; Yang, Bin; Heiland, Steffen; Vieth, Pascal; Voigt, Markus; Schaper, Mirko; Grundmeier, Guido; Schick, Christoph; Kessler, Olaf (Materials & Design)
Additive manufacturing, e.g. by laser powder bed fusion (LPBF), is very attractive for lightweight constructions, as complex and stress-optimised structures integrating multiple functions can be produced within one process. Unfortunately, high strength AlZnMgCu alloys tend to hot cracking during LPBF and thus have not so far been applicable. In this work the melting and solidification behaviour of AlZnMgCu alloy powder variants with particle surface inoculation was analysed by Differential Fast Scanning Calorimetry. The aim is to establish a method that makes it possible to assess powder modifications in terms of their suitability for LPBF on a laboratory scale requiring only small amounts of powder. Therefore, solidification undercooling is evaluated at cooling rates relevant for LPBF. A method for the temperature correction and normalisation of the DFSC results is proposed. Two ways of powder modification were tested for the powder particles surface inoculation by titanium carbide (TiC) nanoparticles: via wet-chemical deposition and via mechanical mixing. A low undercooling from DFSC correlates with a low number of cracks of LPBF-manufactured cubes. It appears that a reduced undercooling combined with reduced solidification onset scatter indicates the possibility of crack-free LPBF of alloys that otherwise tend to hot cracking.
Keywords: Aluminium alloy 7075; Differential fast scanning calorimetry; Solidification; Undercooling; Additive manufacturing

I-AID: Identifying Actionable Information From Disaster-Related Tweets - M. Zahera, Hamada; Jalota, Rricha; Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (IEEE Access)

Knowledge Graphs - Hogan, Aidan; Blomqvist, Eva; Cochez, Michael; d'Amato, Claudia; de Melo, Gerard; Gutiérrez, Claudio; Kirrane, Sabrina; Emilio Labra Gayo, José; Navigli, Roberto; Neumaier, Sebastian; Ngonga Ngomo, Axel-Cyrille; Polleres, Axel; et al. (ACM Comput. Surv.)

Attention to diversity in German CLIL classrooms: Multi-perspective research on students’ and teachers’ perceptions - Siepmann, Philipp; Rumlich, Dominik; Matz, Frauke; Römhild, Ricardo (International Journal of Bilingual Education and Bilingualism)

Bilingualer Unterricht. Aktuelle Herausforderungen und neue Chancen (Fremdsprachen Lehren und Lernen)

Freies Format 2: Nachwuchs-Café (reloaded): Auf dem Weg zur Professur... - Rumlich, Dominik; Matz, Frauke; Juchem-Grundmann, Constanze (Sprache, Kulturen, Identitäten : Umbrüche durch Digitalisierung: 28. Kongress der Deutschen Gesellschaft für Fremdsprachenforschung. Würzburg, 25.-28. September 2019)